The Papers and Writings of Abraham Lincoln, Complete - Lincoln, Abraham, 1809-1865; Choate, Joseph Hodges, 1832-1917; Roosevelt, Theodore, 1858-1919; Schurz, Carl, 1829-1906; Lapsley, Arthur Brooks (Salt Lake City, UT : Project Gutenberg, 2004)
"The Papers and Writings of Abraham Lincoln, Complete" by Abraham Lincoln is an extensive collection of speeches, writings, and correspondence by one of America's most revered presidents, compiled in the early 20th century. The documents are primarily centered around Lincoln's thoughts and policies during the turbulence of the mid-19th century, particularly focusing on his leadership amidst the Civil War and the issues surrounding slavery. This collection serves as a crucial historical record, offering insight not just into Lincoln's presidency but also into the broader socio-political climate of the era. The opening portion introduces readers to Lincoln's profound understanding of governance and human nature, particularly as expressed in a speech following his re-election. It encapsulates his emphasis on unity and shared responsibility during times of national strife, highlighting his moral compass and practical approach to leadership. The introduction by Theodore Roosevelt and the subsequent notes shed light on Lincoln's character and the immense challenges he faced. This section sets the stage for deeper exploration into Lincoln's ideology and actions, paving the way for a comprehensive understanding of the historical implications of his work and thoughts documented throughout the collection. (This is an automatically generated summary.)
Introduction by Theodore Roosevelt -- Editor's Preface by Arthur Brooks Lapsley -- Abraham Lincoln. An Essay by Carl Shurz -- Abraham Lincoln. Memorial Address by Joseph H. Choate -- The writings of Abraham Lincoln.
Release date is 2004-10-01
David Widger
Keywords: Lincoln, Abraham, 1809-1865; United States -- History -- Civil War, 1861-1865; Illinois -- Politics and government -- To 1865; United States -- Politics and government -- 1861-1865; United States -- Politics and government -- 1837-1841; Lincoln-Douglas Debates, Ill., 1858; Lincoln, Abraham, 1809-1865 -- Correspondence; United States -- Politics and government -- 1829-1837; United States -- Politics and government -- 1841-1845; United States -- Politics and government -- 1845-1861